2013
DOI: 10.5951/mathteacher.107.5.0341
|View full text |Cite
|
Sign up to set email alerts
|

Using KenKen to Build Reasoning Skills

Abstract: Through KenKen puzzles, students can explore parity, counting, subsets, and various problem-solving strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…As a result of the study, the classroom teachers had views that mind games played with the students supported the mathematical and logical development of the students. Similar to the results of this study, there are studies concluding that mind games develop mathematical skills (Bottino, Ferlino, Ott & Tavella, 2007 (Reiter, Thornton & Vennebush, 2014;Yöndemli & Doğan-Taş, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As a result of the study, the classroom teachers had views that mind games played with the students supported the mathematical and logical development of the students. Similar to the results of this study, there are studies concluding that mind games develop mathematical skills (Bottino, Ferlino, Ott & Tavella, 2007 (Reiter, Thornton & Vennebush, 2014;Yöndemli & Doğan-Taş, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…It is possible to talk about the effects of mind games on children in cognitive, affective and social areas. When considered cognitively, mind games were revealed to improve students' thinking skills (Bottino & Ott, 2006;Kula, 2020), mathematical skills (Bottino, Ferlino, Ott & Tavella, 2007;Erdoğan, Eryılmaz-Çevirgen & Atasay, 2017;Saygı & Alkaş-Ulusoy, 2019;Ulusoy, Saygı & Umay, 2017), mathematical reasoning skills (Reiter, Thornton & Vennebush, 2014;Yöndemli & Doğan-Taş, 2018), problem solving and reasoning skills (Bottino & Ott, 2006;Kurbal, 2015;Şahin, 2019), critical thinking skills (Dewar, 2012;Savaş, 2019), creative thinking skill (Ott & Pozzi, 2012), spatial skills (Zeybek & Saygı, 2018;Yang & Chen, 2010), attention and visual perception (Altun, 2017 ), and strategy use (Best, 1990). Mind games also improve geometric thinking level (Dokumacı-Sütçü, 2018;Siew & Abdullah, 2012) and mental skill level (intensifying attention, strategic thinking, analysis, establishing the part-whole relationship, visual perception and benefiting from clues) (Marangoz & Demirtaş, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Strom and Barolo (2011) examined the effect of the game they used in the study (mastermind) on reasoning skills and observed that it had a positive effect. Reiter, Thornton and Vennebush (2014) mentioned in their study that the 'kendoku' game improved the reasoning skills. They point out that the reasoning skills important in mathematics and other lessons as well as everyday life, are improved through playing this game.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 98%
“…Experts have spoken about the important effects of mind games on the learning (Kirriemuir & McFarlane 2004;Mitchell &Savill -Smith 2004) and cognitive development (Ghoneim, & Essam, 2012;Sigirtmac, 2016;Turkoglu & Uslu, 2016) of preschool and primary school children. Reiter, Thornton and Vennebush (2014) reported that children could meaningfully reason with numbers and operations thanks to the kenken, a sudoku variant. (Soduko is a well-known game of the mind games family).…”
Section: Mind (Intelligence) Gamesmentioning
confidence: 99%